Former church of Vaires - Auteur inconnu (Wikimedia Commons, 1910)
Carte postale ancienne issue de Wikimedia Commons. Titre: Former church of Vaires. The former church Sainte-Agathe of Vaires-sur-Marne (Seine-et-Marne, France) in the 1910s on an old postcard. Since, it has been destroyed in 1935 and replaced by a modern church.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église; Carte postale